Potential of Crop Residues for Energy Production in Nepal - Adhikari, Narayan Prasad; Denich, Manfred (Journal of the Institute of Engineering, 2020)
The study aims at assessing the availability of crop residues for energy production in lowland, hill and mountain districts of Nepal. Rice, wheat, maize, millet and barley are included in the study that is based upon two different household surveys: (i) interviews conducted in 240 households to obtain key information about practices of crop harvesting, (ii) determination of the quantity of the main crops, their residues and alternative uses of the latter conducted in 27 households. Apart from the foremost use as fodder, there are five major uses of crop residues: building material, burning on the field, mulching of the field, selling and energy generation. Despite the higher amount of crop residues in the lowland (954 kg dry matter per capita and year) than in the hill district (547 kg capita-1 yr-1 ), the amount of crop residues used for energy generation higher in the hill (207 kg capita-1 yr-1 ) than in the lowland district (152 kg capita-1 yr-1 ). In the mountain district, the crop residue production is 263 kg capita-1 yr-1 , of which 26 kg capita-1 yr-1 are used for energy generation. The annual per capita energy equivalent from crop residues in the lowland, hills and mountains are 2.49 GJ, 3.42 GJ and 0.44 GJ which represent 30%, 33% and 3%, respectively, of the total annual cooking energy consumption.